RETRACTED: Integration of Neuroscience and Entrepreneurship: A Systematic Review and Bibliometric Analysis - Liu, Weiwei; Xu, Yimeng; Xu, Tiantian; Ye, Zijian; Yang, Jiani; Wang, Yan (Frontiers in Psychology, 2022)
In this study, we investigated the integration between neuroscience and entrepreneurship. First, we explored the concept of neuroentrepreneurship and the investigation of neuroentrepreneurship using scientific research methods. Second, we constructed a road map for entrepreneurial researchers interested in conducting neuroentrepreneurship-related research. This is an emerging research area; therefore, to more clearly analyze the dynamics of the research trends, we used a bibliometric method to capture patterns in current publications on subjects related to neuroentrepreneurship, examining papers published between 1999 and 2021 using the keywords “neuroscience” and “entrepreneurship” or “neuroentrepreneurship.” To identify the keywords, we used two academic databases—the Social Science Citation Index and Science Citation Index—accessed through the Web of Science website. The three keywords were identified from studies integrating neuroscience with entrepreneurship. After carefully reviewing the research papers, we identified neuroentrepreneurship as a novel research area. The outcomes of this study provide a guide for describing the theoretical connection between neuroscience and entrepreneurship. In the future, this field of study should be empirically investigated.